2018
DOI: 10.1021/acssynbio.7b00446
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective and Low-Cost MicroRNA Detection with CRISPR-Cas9

Abstract: MicroRNAs have been reported as related to multiple diseases and have potential applications in diagnosis and therapeutics. However, detection of miRNAs remains improvable, given their complexity, high cost, and low sensitivity as of currently. In this study, we attempt to build a novel platform that detects miRNAs at low cost and high efficacy. This detection system contains isothermal amplification, detecting and reporting process based on rolling circle amplification, CRISPR-Cas9, and split-horseradish pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 33 publications
(50 reference statements)
0
95
0
Order By: Relevance
“…The above‐reported examples have outlined the tremendous potential that CRISPR‐based technologies have to detect many different types of nucleic acids, including genomic DNA, nongenomic DNA, RNA, pathogenic virus and pathogenic bacteria. Moreover, the CRISPR‐based detection methods show great advances in terms of cost, for example, the cost for RCH and SHERLOCK is about $1.727/test (Qiu et al, 2018) and $0.61/test (Gootenberg et al, 2017) respectively. According to Table 1, we found that the CRISPR‐Cas9 system is still the most commonly used system in the field of nucleic acid detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above‐reported examples have outlined the tremendous potential that CRISPR‐based technologies have to detect many different types of nucleic acids, including genomic DNA, nongenomic DNA, RNA, pathogenic virus and pathogenic bacteria. Moreover, the CRISPR‐based detection methods show great advances in terms of cost, for example, the cost for RCH and SHERLOCK is about $1.727/test (Qiu et al, 2018) and $0.61/test (Gootenberg et al, 2017) respectively. According to Table 1, we found that the CRISPR‐Cas9 system is still the most commonly used system in the field of nucleic acid detection.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, considerable efforts have been devoted to engineering Cas nucleases to construct novel nucleic acid detection platforms, such as the dCas9‐split horseradish peroxidase (HRP) fusion protein (Qiu et al, 2018) and the dCas9‐split‐luciferase fusion protein (Y. Zhang et al, 2017). Recently, the Li group constructed an mRNA‐sensing platform by engineering a conditional sgRNA, rather than a Cas9 protein (Figure 4a; Y. Li, Teng, Zhang, Deng, & Li, 2019).…”
Section: Detection Of Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although much attention is given to the use of CRISPR/Cas to correct genetic diseases, CRISPR can also constitute a diagnostic tool. CRISPR systems have been used for the detection of microRNA biomarkers, and for minor allele enrichment in cell‐free DNA prior to diagnostic testing in NSCLC patients . Such diagnostic applications may be more feasible than in vivo gene editing or cell transplantation strategies, and could have immediate and positive impact in clinical settings.…”
Section: Crispr/cas Gene Therapy For Respiratory Diseasesmentioning
confidence: 99%
“…The rise of CRISPR Cas9 based approaches for biosensing nucleic acids has opened up a broad diagnostic portfolio for CRISPR products beyond their standard genome editing abilities 1,2 . In recent times, CRISPR components have been successfully used for detecting a wide variety of nucleic acid targets such as those obtained from pathogenic microorganisms or disease-causing mutations from various biological specimens [3][4][5][6][7][8][9][10] . At the heart of such a detection procedure lies the property of CRISPR proteins to accurately bind to target DNA or RNA, undergo conformational changes leading to cleavage of targets generating a reporter-based signal outcome [11][12][13][14][15] .…”
mentioning
confidence: 99%